2018
DOI: 10.1021/acscatal.7b03768
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation Initiated by In Situ Dimerization of the Molecular Ru(pdc) Catalyst

Abstract: The mononuclear ruthenium complex [Ru(pdc)L 3 ] (H 2 pdc = 2,6-pyridinedicarboxylic acid, L = N-heterocycles such as 4-picoline) has previously shown promising catalytic efficiency toward water oxidation, both in homogeneous solutions and anchored on electrode surfaces. However, the detailed water oxidation mechanism catalyzed by this type of complex has remained unclear. In order to deepen understanding of this type of catalyst, in the present study, [Ru(pdc)(py) 3 ] (py = pyridine) has been synthesized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The complex has a highly distorted octahedral geometry owing to the strain imposed by the pdc 2− meridional ligand with an O–Ru–O angle of 157° compared with the 180° angle expected for an ideal octahedron. It shows similar bond distances and angles as those reported for related complexes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex has a highly distorted octahedral geometry owing to the strain imposed by the pdc 2− meridional ligand with an O–Ru–O angle of 157° compared with the 180° angle expected for an ideal octahedron. It shows similar bond distances and angles as those reported for related complexes …”
Section: Resultsmentioning
confidence: 99%
“…In this work, we explored the water oxidation catalytic activity of Ru complexes containing the meridional tridentate dianionic ligand 2,6‐pyridinedicarboxylato (pdc 2− ), which can show different coordination modes . For instance, it can coordinate in a tridentate κ‐N 1 O 2 meridional fashion, provide a strong sigma bond donation to the metal center, and it can also bind in a bidentate κ‐N 1 O 1 mode leaving a pendant carboxylate . We report the preparation, purification, and isolation of two new Ru complexes [Ru III (pdc‐κ 3 ‐N 1 O 2 )(bpy)Cl] ( 1 III ) and [Ru II (pdc‐κ 2 ‐N 1 O 1 )(bpy) 2 ] ( 2 II ) shown in Scheme , which contain one or two neutral bidentate 2,2′‐bipyridine (bpy) ligands in addition to the pdc 2− ligand, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sakai et al suggested that the oxido-bridged trinuclear species obtained in situ in the air conditions could serve as an active catalyst for photochemical oxygen evolution. Given that recent reports have renewed interest toward the construction of oxo-bridged water oxidation catalysts (Concepcion et al, 2015;Daniel et al, 2018;Jiang et al, 2018;Lopez et al, 2014), we become particularly interested in designing oxo-bridged molecular catalysts and understanding the cooperative action of substrate water access, proton release, and dioxygen formation in oxo-bridged molecular clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] During the past few decades, extraordinary efforts have been dedicated to the synthesis of manganese-based molecular complexes to mimic the structure and function of the OEC. [6][7][8][9][10] Other transition metals were also used for the synthesis of water oxidation catalysts, including Ru, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ir, [25,26] Fe, [27][28][29][30][31] Co, [32][33][34] Ni, [35][36][37] and Cu. [38][39][40] Recently,the Llobet group disclosed the synthesisofaheterotrinuclear Ru 2 Mn complex A 0 {[Ru II (tpy)] 2 (m-[Mn II (bpp) 2 ]) (OAc) 2 } 2 + [tpy = 2,2':6',2''-terpyridine, bpp = 3,5-bis(2-pyridyl)pyrazolate].…”
Section: Introductionmentioning
confidence: 99%